Re: Percutaneous Nephrolithotomy in Horseshoe Kidneys: Results of a Multicentric Study - ŞENER, TARIK EMRE; TANIDIR, YILÖREN (My University, 2022)
This retrospective, multicenter study of patients with horseshoe kidneyssubjected to percutaneous nephrolithotomy (PCNL) demonstrated some expected findings: those withhigher stone burden less apt to be cleared of stone (stone-freeþresidual fragments<4 mm).Increasing body mass index was shown to negatively impact this parameter which has not beenreported for the generic patient subjected to PCNL. These results also demonstrate that supine PCNLcan be undertaken safely and effectively in this cohort.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology